Top of the podium, at what cost? injuries in female international elite climbers - Grønhaug, G.; Joubert, L. M.; Saeterbakken, A. H.; Drum, S. N.; Nelson, M. C. (Frontiers in Sports and Active Living, 2023)
Competitive sport climbing has made its way to the Olympic stage. This prestige has brought about route setting and training alterations which presumably affect injury epidemiology. Most of the climbing injury literature contains male climbers and lacks high performing athletes. Studies with both female and male climbers, rarely included separate analyses for performance level or sex. Therefore, injury concerns for elite female competitive climbers are impossible to discern. A former study examined the prevalence of amenorrhea in elite international female climbers (n=114) and reported that 53.5% had at least one injury in the past 12 months, but injury details were excluded. This study’s aim was to report these injury details and their associations with BMI, menstrual status and eating disorders of the cohort. Methods Online survey was emailed to competitive female climbers recruited through the IFSC database between June and August 2021. Data was analyzed using Mann-Whitney U, Chi square and logistic regression. Results 229 registered IFSC climbers opened the questionnaire and 114 (49.7%) provided valid responses. Respondents (mean±SD; age= 22.9±5 y) represented 30 different countries and more than half (53.5%, n=61) reported an injury in the prior 12 months with the majority in shoulders (37.7%, n=23) and fingers (34.4%, n=21). Injury prevalence in climbers with amenorrhea was 55.6% (n = 10). BMI was not a significant predictor of injury risk (OR=1.082, 95% CI: 0.89, 1.3; p=0.440) while accounting for current ED over the past 12 months. However, the odds ratio for having an injury was doubled for those with an ED (OR=2.129, 95% CI 0.905, 5.010; p=0.08). Conclusion With over half reporting recent injuries (< 12 months) mostly to shoulders and fingers, development of new strategies for injury prevention in competitive female climbers are warranted. In addition, climbers with disordered eating behaviors and/or menstrual disturbances might be more prone to injury. More research in this population is required. Suitable screening to prevent these health issues and proper monitoring of these athletes are paramount to long-term athlete success.